GM-005 Hospital transfer is a critical period. Oncology pharmacy unit users' evaluations. (14th February 2016) - Zapico, I; Llorente, A; Sacristan, MP; Gomez de Segura, L; Martinez, A; Alaguero, M; Iglesias, T
Abstract : Background: Because of the complex transfer process of one university hospital, it became necessary for the pharmacy service to distribute its activities in both locations (old and new) for 6 weeks. A system for validation and distribution to provide adequate service to patients treated at the facilities of the new hospital was established. Purpose: To assess the level of satisfaction and, if feasible, to identify reasons for dissatisfaction of hospital staff during the transfer process regarding the services provided by the oncology pharmacy unit (OPU). Material and methods: Cross sectional study through a self-administered questionnaire distributed to hospital staff to which the preparations made in the OPU are intended. The document contained the same closed questions regarding the pre- and post-transfer periods. In addition, a rating scale of 5 points to evaluate the service provided by the OPU was included. Results: 38 professionals answered the questionnaire (16 physicians, 15 nurses and 7 nursing assistants). Most (86.8%) developed their activity in outpatient clinics. Prior to the transfer, 92.1% considered their personal activity would be affected somewhat or a lot and 76.3% considered that the security of the patients would be affected somewhat or a lot. Following the transfer, the response rates for these same items were lower (84.2% and 42.1%, respectively). The main concerns expressed a priori by respondents were regarding waiting times (n = 28) and potential errors in transcription and preparation (n = 11). Only 3 respondents reported problems a posteriori, always in relation to waiting times. The assessment of the pharmacist performance was good or very good in 89.4% of cases. Evaluation of the cover slot and compliance with the agreed schedule was good or very good in 68.4% of cases. The overall assessment of this period was better than expected in 65.8% of cases. Conclusion: The performance of the OPU, adapting its activity to the provisional situation of the transfer in order to provide quick, safe and quality patient care, was highly valued by the professionals. Previous expectations were improved. Problems were reported by a few respondents and were always related to waiting times, and never to quality of care or patient safety. No conflict of interest.